Acetylene and Diacetylene Functionalized Covalent Triazine Frameworks as Metal‐Free Photocatalysts for Hydrogen Peroxide Production: A New Two‐Electron Water Oxidation Pathway. Issue 2 (29th November 2019) - Chen, Liang; Wang, Lei; Wan, Yangyang; Zhang, Ying; Qi, Zeming; Wu, Xiaojun; Xu, Hangxun
Abstract: Metal‐free polymer photocatalysts have shown great promise for photocatalytic H2 O2 production via two‐electron reduction of molecular O2 . The other half‐reaction, which is the two‐electron oxidation of water, still remains elusive toward H2 O2 production. However, enabling this water oxidation pathway is critically important to improve the yield and maximize atom utilization efficiency. It is shown that introducing acetylene (CC) or diacetylene (CCCC) moieties into covalent triazine frameworks (CTFs) can remarkably promote photocatalytic H2 O2 production. This enhancement is inherent to the incorporated carbon–carbon triple bonds which are essential in modulating the electronic structures of CTFs and suppressing charge recombinations. Furthermore, the acetylene and diacetylene moieties can significantly reduce the energy associated with OH* formation and thus enable a new two‐electron oxidation pathway toward H2 O2 production. The study unveils an important reaction pathway toward photocatalytic H2 O2 production, reflecting that precise control over the chemical structures of polymer photocatalysts is vital to achieve efficient solar‐to‐chemical energy conversion. Abstract : Covalent triazine frameworks incorporated with acetylene and diacetylene moieties exhibit a unique two‐electron water oxidation pathway toward H2 O2 production in addition to the two‐electron oxygen reduction pathway. Both experimental and theoretical investigations reveal that carbon–carbon triple bonds are critical to modulate the electronic structures and provide active sites for photocatalytic H2 O2 production.